2013
DOI: 10.1002/jgrf.20043
|View full text |Cite
|
Sign up to set email alerts
|

Potential dust emissions from the southern Kalahari's dunelands

Abstract: [1] The Southern Hemisphere shows relatively low levels of atmospheric dust concentrations. Dust concentrations could, however, increase as a result of losses of vegetation cover in the southern Kalahari. There is some evidence of an ongoing remobilization of stabilized dunefields in the southern Kalahari where dune crests with sparse vegetation cover are reactivated during dry and windy periods, a phenomenon that is predicted to intensify with increased land degradation, overgrazing, and droughts. Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…Although the iron in the fine fraction appears to be not enriched, atmospheric processing that leads to increase in bioavailability of iron could play an important role in determining if iron in dust from Southern Africa will have major impacts on ocean productivity. A recent study shows that the potential dust flux from the southern Kalahari due to devegetation is about 0.42 Tg yr À1 (e.g., Bhattachan et al, 2013), which may not be a substantial contribution in the global context however, an increased delivery of soluble iron, TN and TP in dust from the southern Kalahari to the Southern Ocean could have significant impacts on ocean productivity. The iron enrichment ratio values for pan sediments (both at the Etosha and Makgadikgadi pans) are variable; with larger enrichment ratio found in sediments sampled from the surface of the pan.…”
Section: Bioavailability Of Ironmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the iron in the fine fraction appears to be not enriched, atmospheric processing that leads to increase in bioavailability of iron could play an important role in determining if iron in dust from Southern Africa will have major impacts on ocean productivity. A recent study shows that the potential dust flux from the southern Kalahari due to devegetation is about 0.42 Tg yr À1 (e.g., Bhattachan et al, 2013), which may not be a substantial contribution in the global context however, an increased delivery of soluble iron, TN and TP in dust from the southern Kalahari to the Southern Ocean could have significant impacts on ocean productivity. The iron enrichment ratio values for pan sediments (both at the Etosha and Makgadikgadi pans) are variable; with larger enrichment ratio found in sediments sampled from the surface of the pan.…”
Section: Bioavailability Of Ironmentioning
confidence: 98%
“…Recent studies have assessed the potential of the southern Kalahari to become an important dust source in the Southern Hemisphere (e.g., Bhattachan et al, 2012Bhattachan et al, , 2013 and dust from these dunefields will commonly reach the Southern Ocean (Bhattachan et al, 2012). The remobilization of stabilized dunes in the southern Kalahari can result in dust emissions comparable to the currently active Makgadikgadi and Etosha pans (Bhattachan et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…The percentage of clay and silt sized particles is greater in the Mallee sediments than in the southern Kalahari interdunes (for southern Kalahari grain size data see Bhattachan et al16). However, we note that the percentage of clay and silt sized particles in soil is not a robust measure of dust generating potential of a source and other mechanisms such as sandblasting, and breaking up of loose aggregates during erosion could affect the dust generating potential43.…”
Section: Discussionmentioning
confidence: 99%
“…Land-use practices such as deforestation and overgrazing have potential to activate new dust sources in the Southern Hemisphere1415 with significant impacts to downwind soils and ecosystems. Potential new dust sources that could be activated as an effect of land use have been identified in Patagonia14, the Kalahari16, while in Australia the effect of land use on dust emissions has seldom been investigated in the context of its impact on ocean productivity.…”
mentioning
confidence: 99%
“…In the southern Kalahari, dune mobilization occurs during dry and windy periods when vegetation cover decreases below ;14% (Wiggs et al 1995), though a dramatic increase in aeolian transport is observed already when vegetation v www.esajournals.org cover is less than 40% (e.g., Bhattachan et al 2013). Indeed, bare, mobile dunes are ubiquitous in the southern Kalahari and are usually found closer to villages on communal lands and overgrazed farms.…”
Section: Land Use In the Southern Kalaharimentioning
confidence: 99%